2016
DOI: 10.2459/jcm.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between intermediate and severe coronary stenoses and clinical outcomes of an OCT-guided PCI strategy

Abstract: aAims We compared optical coherence tomography (OCT) features of intermediate and severe coronary stenoses in patients with stable angina and acute coronary syndrome (ACS), and tested the clinical impact of an OCT-based strategy for treating intermediate stenoses.Methods The study enrolled 135 consecutive patients with either ACS or stable angina and a single de-novo coronary stenosis. Patients were divided into two groups: intermediate stenosis defined as quantitative coronary angiography percentage narrowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…OCT performed after angioplasty is better able to demonstrate the stent-vessel wall association as well as visualize individual stent struts and their distance from the vessel wall ( 10 , 17 , 27 , 35 ). The present study results indicated that dissections were not identified by CAG; however, they were detected by OCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OCT performed after angioplasty is better able to demonstrate the stent-vessel wall association as well as visualize individual stent struts and their distance from the vessel wall ( 10 , 17 , 27 , 35 ). The present study results indicated that dissections were not identified by CAG; however, they were detected by OCT.…”
Section: Discussionmentioning
confidence: 99%
“…It is a particularly attractive technique because it provides real-time images and microstructural information on the tissues ( 13 , 14 ). Furthermore, it can be used to provide a detailed analysis of the coronary artery wall, including plaque characterization, thin-cap fibroatheroma (TCFA) and vulnerable plaque identification, and assessments of the vascular response to PCI, which may be responsible for acute coronary events ( 11 , 12 , 15 17 ). Considerable evidence currently indicates that the early use of OCT reveals various abnormal vessel reactions associated with stent implantation, such as stent malapposition, suboptimal stent deployment, thrombus, tissue prolapse, and edge dissection ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation